Caputo fractional q-difference equations in Banach spaces - Salim, Abdelkrim; Abbas, Said; Benchohra, Mouffak; Lazreg, Jamal Eddine (Journal of Innovative Applied Mathematics and Computational Sciences, 2023)
This paper aims to explore the existence results of a certain type of Caputo fractional qq-difference equations in Banach spaces. To achieve this goal, we employ a fixed point theorem that relies on the concept of measure of noncompactness and the convex-power condensing operator. We give an illustrative example in the last section.